The logic of anatomy: dissective rationality and the difference of incarnation - Kornu, Kimbell (2017)
My thesis is that the tendency of modern medicine to reduce patients into causes to be mastered rather than persons to be treated does not stem from post-Enlightenment developments but rather lies within the beginnings of Western medicine itself, in what I call the anatomical rationality. I follow the development of this rationality through Hippocrates, the beginnings of anatomical dissection in Aristotle and Herophilus, and the theological translation of anatomy by Galen. I further show how this anatomical rationality that arises from medicine then transforms into dissective analysis that applies to theological and philosophical discourse, as seen paradigmatically in Nestorianism and the ontological logic of Avicenna. I argue that this anatomical rationality is a totalizing approach to knowing that creates new dualisms, such that nothing can escape the dissective gaze, God and man included. I suggest that the way to overcome the totalizing effects of the anatomical rationality is turning to the Incarnation of Christ, the God-man, who provides both the metaphysical ground and imagination for paradox and mystery, thereby protecting the integrity of God and man.